MicroRNA-126-3p Attenuates Intracerebral Hemorrhage-Induced Blood-Brain Barrier Disruption by Regulating VCAM-1 Expression - Fu, Xi; Niu, Tiesheng; Li, Xiaodong (Frontiers in Neuroscience, 2019)
Background miR-126 is closely related to the occurrence of various complications after intracerebral hemorrhage (ICH), but the molecular mechanism is not fully elucidated. This study aimed to explore the mechanism of miR-126-3p in alleviating brain injury after ICH. Methods Serum miR-126-3p levels were compared between patients with IHC and healthy controls. A rat model of ICH was generated by intracerebral injection of Type VII collagenase. The rats were intracerebral injected with miR-126-3p mimics or negative control miRNA. Rat brain microvascular endothelial cells (BMECs) were used as a cell model of blood-brain barrier (BBB), and validated by immunofluorescence staining of Factor VIII. The BBB permeability of BMECs after miR-126-3p antagomir transfection was determined by FITC-dextran 20 through a confluent BMECs layer (measured over 120 min). The binding site of miR-126-3p in the 3'UTR of VCAM-1 was predicated by TargetScan, and verified by dual luciferase reporter assay. The expression levels of miR-126-3p and vascular cell adhesion molecule-1 (VCAM-1) in rat brain tissues and BMECs were measured by real-time PCR or western blotting. Results Serum miR-126-3p level was markedly down-regulated in patients with ICH. The rats with ICH had decreased miR-126-3p levels in serum and hemorrhagic area, while those changes were reversed by the treatment with miR-126-3p mimic. VCAM-1 is a direct target of miR-126-3p, and VCAM-1 expression in hemorrhagic area was down-regulated by the administration of miR-126-3p mimic in rats. Inhibition of miR-126-3p by anti-miR126 treatment in BMECs resulted in barrier leakage. Conclusions miR-126-3p attenuates intracerebral hemorrhage-induced blood-brain barrier disruption, which is associated with down-regulated expression of VCAM-1 in hemorrhagic area.